Factors Associated With Complaints of Disorders Hearing In Workers In The Machine Section of PT. Fertilizer Iskandar Muda Lhokseumawe In 2022 - Fhitriana Pakpahan, Suzan; Nasution, Siti Khairunnisa; Hutagalung, Suzanne C.; Agustiawan, Agustiawan (Pena Cendekia Insani, 2024)
Introduction: Technological advances in the machinery sector, have succeeded in creating a variety of machine products that in operation often produce noise that must be faced by employees in doing work. Objective: The purpose of this study was to determine the factors associated with complaints of hearing loss in workers at PT. Pupuk Iskandar Muda Lhokseumawe. Method: This study used descriptive with a cross sectional approach. The study population was all workers as many as 200 workers with a sample of 133 workers taken using simple random sampling techniques. Data analysis using univariate, bivariate analysis with statistical logistic regression tests. Results: The variables worker age = 0.000, length of exposure = 0.000, working period = 0.000, noise intensity = 0.000, ear protection equipment = 0.000, which means worker age, length of exposure, noise intensity, ear protection equipment (APT). Conclusion: This study is that there is a relationship between worker age, length of exposure, length of service, noise intensity and ear protection equipment with complaints of hearing loss in machine part workers. It is expected that workers can comply with the regulations set by the factory and pay more attention to occupational safety and health.